Reproductive performance of crossbred dairy cows under smallholder condition in Ethiopia (African Journal of Dairy Farming and Milk Production, 2013)
A study was carried out to assess the reproductive performance of crossbred dairy cows under smallholder conditions in Asella town, Oromia regional state, Ethiopia. A total of sixty crossbred dairy cow farmers that owned 3 to 5 cows were interviewed using a structured questionnaire to collect information on age at first service, age at first calving, days open and calving interval. Simultaneously, reproductive performances of 250 crossbred dairy cows of the selected farmers were studied. The overall estimated mean values for age at first service, age at first calving, calving interval, days open, and number of service per conception were 24.9±3.8 months, 34.8±4 months, 372.8±5.9 days, 85.6±5.6 days and 1.52±0.9, respectively. In this study, 35% of the respondents’ came across return rate after the first service in their crossbred dairy cows. In general, the overall observed reproductive performance of crossbred dairy cows was found to be promising considering the management situation and limited supplemental feed utilized in the area. Thus, a sustainable extension service should be established in order to improve animal feed resources management, efficient artificial insemination service and animal health care to bridge the existing gaps.